1989
DOI: 10.1080/10862968909547657
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Writing in a Reader-Based and Text-Based Mode on Students' Understanding of Two Short Stories

Abstract: This study examined how personal versus formal writing tasks affect what students take from literary text. The writing samples produced by sixty-five 10th-grade students in response to two short stories were analyzed for quality of response, audience, function, syntactic complexity, fluency, and types of response statements. Findings indicated that the reader-based or personal writing tasks enabled the students to produce qualitatively more effective responses that tended to be more fluent and constructed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Personal responses and formal writing (Marshall, 1987;Newell, Suszynski & Weingart, 1989), but also guided journal writing (Wong, Kuperis, Jamieson, Keller & Cull-Hewitt, 2002) are metatextual writing activities. The writing activities on language proposed by Boscolo and Carotti (2003), and the joint and individual writing activities used by Rose and Martin (2012) are hypertextual.…”
Section: Writing In French Literature Classes: Conceptual Distinctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal responses and formal writing (Marshall, 1987;Newell, Suszynski & Weingart, 1989), but also guided journal writing (Wong, Kuperis, Jamieson, Keller & Cull-Hewitt, 2002) are metatextual writing activities. The writing activities on language proposed by Boscolo and Carotti (2003), and the joint and individual writing activities used by Rose and Martin (2012) are hypertextual.…”
Section: Writing In French Literature Classes: Conceptual Distinctionsmentioning
confidence: 99%
“…The two latter yield higher posttest scores. In a similar way, Newell, Suszynski and Weingart (1989) compared personal and formal writings on two short stories. The first ones resulted in longer and more fluent texts, where the teachers became dialogue partners.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, response has been used as a method of determining a reader's processing of literature, not exposition (e.g., Cullinan, Harwood, & Galda, 1983;Fish, 1980;Golden & Guthrie, 1986;Holland, 1975;Newell, Suszynski, & Weingart, 1989;Purvis & Rippere, 1968;Tompkins, 1980). Response studies, generally, have suggested that individual readers have characteristic ways of responding (Galda, 1980;Holland, 1975;Petrosky, 1975), but that response behavior may also be learned (Purves, 1981), for example, from classroom experiences (Wilson, 1966).…”
Section: Responsementioning
confidence: 99%
“…Several researchers have proposed classifying responses to text as reader-based or text-based (Applebee, 1978;Englert, Hieben, & Stewart, 1988;Galda, 1983;Golden & Guthrie, 1986;Newell et al, 1989;Reis & Spekman, 1983;Roller, 1985;Sadoski, Goetz, & Kangiser, 1988). Although the ideas about how to classify reader-based and text-based responses vary across researchers, it does appear that there is some agreement with the idea that readers approach the interpretation of text using two sources-the cues from the text itself and their own experiences, attitudes, personalities, and beliefs.…”
Section: Reader-basedltext-based Reactionsmentioning
confidence: 99%
See 1 more Smart Citation